Life events and social support in a 1-year preceding panic disorder - Batinić, Borjanka (Array, 2009)
The aim of the study was to examine the frequency and class of life events, as well as social support, in patients with panic disorder (with/without agoraphobia) (PD/PDA) in a 1-year period preceding the onset of panic attacks. The study sample included 40 patients (PD/PDA) (of an average age of 39.25, SD 6.96), and 40 matched healthy controls (M 37.50, SD 8.05). The following instruments were applied: DSM-IV criteria for PD/PDA, Stressful Life Events Scale, Social Support Index (SSI), Family Coping Coherence Index (FCCI), Relative and Friend Support (RFS) and Family Hardiness Index (FHI). The study was retrospective. Results: Patients with PD/PDA compared to the healthy controls, had significantly increased frequency of negative life events (M 3.8, min 0, max 11) (p<0.05)